1991
DOI: 10.1007/bf00965694
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia-induced astrocyte swelling in primary culture

Abstract: The effect of ammonia on water space of astrocytes in culture was determined as a means of studying the neurotoxicity of ammonia in fulminant hepatic failure (FHF). Treatment of primary astrocyte cultures obtained from neonatal rat cortices with 10 mM NH4Cl for 4 days resulted in a 29% increase in astrocytic water space, as measured by an isotopic method utilizing 3-O-methyl-[3H]-glucose. This effect was time- and dose-dependent. The ammonia-induced swelling was reversible as the water space in cultures treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
103
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(111 citation statements)
references
References 23 publications
5
103
0
3
Order By: Relevance
“…Increased brain water content has been described in both normal (Takahashi et al, 1991) and in portacaval shunted (Blei et al, 1994) rats infused with ammonia as well as in rats with liver devascularization (Rose et al, 1999). Similar results have been described in vitro following the exposure of cultured astrocytes to ammonia (Norenberg et al, 1991). Furthermore, prevention of brain edema in rats with ALF has been shown with ammonia-lowering strategies (Cordoba et al, 1999;Rose et al, 1999Rose et al, , 2000.…”
Section: Calcium-independent Glutamate Releasesupporting
confidence: 62%
“…Increased brain water content has been described in both normal (Takahashi et al, 1991) and in portacaval shunted (Blei et al, 1994) rats infused with ammonia as well as in rats with liver devascularization (Rose et al, 1999). Similar results have been described in vitro following the exposure of cultured astrocytes to ammonia (Norenberg et al, 1991). Furthermore, prevention of brain edema in rats with ALF has been shown with ammonia-lowering strategies (Cordoba et al, 1999;Rose et al, 1999Rose et al, , 2000.…”
Section: Calcium-independent Glutamate Releasesupporting
confidence: 62%
“…In addition, marked intracellular swelling of the perivascular astroglial foot processes was present in patients who died in ALF-induced coma (Kato et al, 1992). In vitro experiments have also reported astrocyte swelling, by assessing the intracellular space using [ 3 H]-3-O-methylglucose ( Norenberg et al, 1991), or by microscopic measurements of cellular volume ( Hirrlinger et al, 2008), following the addition of pathogenic factors associated with HE. In CLD, astrocytes present a characteristic morphology, known as Alzheimer type II astrocytosis: large, swollen cells with enlarged swollen nuclei and cytoplasm, margination of chromatin, mitochondrial and rough endoplasmic reticulum proliferation and accumulation of glycogen ( Norenberg, 1977).…”
Section: Astrocyte Swelling and Brain Edema In Liver Disease/failurementioning
confidence: 99%
“…In ALF, brain ammonia may reach millimolar concentrations, 7 and exposure of various in vitro brain preparations to millimolar concentrations of ammonia results in significant cell swelling. 8,9 Hyperammonemia is a feature of Reye' s Syndrome 10 and congenital urea cycle enzymopathies, 11 conditions in which cerebral edema is also consistently observed.Previous studies showed that hypothermia extended the survival time and prevented the development of brain edema in rats with ALF. 12 Furthermore, mild hypothermia (33°C-35°C) has been shown to be neuroprotective in experimental models of traumatic 13 and ischemic brain injury.…”
mentioning
confidence: 99%